Smartening the Grid in Developing Countries : Emerging Lessons from World Bank Lending - Nangia, Varun (World Bank, Washington, DC, 2016)
Since fiscal year 2010 the World Bank has supported 20 smart grid projects in 19 countries and all six Bank regions. Valued at 960 million dollars - a quarter of all Bank support for transmission and distribution during the period — the projects have focused on advanced metering, distribution automation, and supervisory control and data acquisition for energy and distribution management systems. Some of these projects are still under implementation, but task teams are learning valuable lessons about how to implement smart grid projects most effectively.